Manufacturing process re-engineering design implementation using computer simulation model - Wirabhuana, Arya (2006)
Simulation is one of tools that have been used widely in several manufacturing areas and organizations as well as in automotive industries. Using a valid simulation model may possible give several benefit and advantages in creating better manufacturing design in order to improve the system performances. This project is concerning in implementing a computer based simulation model to design Manufacturing Process Re-engineering scenarios for performances improvement. The basic problem addressed by this project is that the current manufacturing system performances have to be improved to deal with the business environment. Project’s objective is to develop/design four improvement alternatives design using Valid Computer Simulation model. Three approaches which are: Line Balancing, Facilities re-layout and process enhancement, and manufacturing process automating were applied as the foundation in creating improvement scenarios of the real system. Simulation modeling formally followed the enhanced Discrete Event Simulation methodologies. Simulation models were developed using Process Oriented Simulation Software which is ARENA version 7.1 while Statfit and Microsoft Excel software package were used for statistical analysis. Project’s case study was taken from the Job Shop Manufacturing line / Intermittent Process Industries in Body welding and metal finish operations of Isuzu N-series Truck assembly line of PT. Pantja Motor, Indonesia. The project deliverable might be differ into the initial simulation model of current system and four Manufacturing Process Re-engineering scenarios that will be based on three approaches as mentioned above. Constraints and challenges in conducting the project seemed might be reduced wisely, so that the whole project outcome and deliverables are still achieved appropriately